Curvularin Isolated From Phoma macrostoma Is an Antagonist of RhlR Quorum Sensing in Pseudomonas aeruginosa - Choi, Ha-Young; Le, Duc Dat; Kim, Won-Gon (Frontiers in Microbiology, 2022)
Quorum sensing (QS) is an attractive target for the treatment of multidrug-resistant Pseudomonas aeruginosa, against which new antibiotics are urgently needed. Because LasR is at the top of the QS hierarchy controlling Rhl and PQS systems, most QS inhibitors have been targeted to LasR. However, it has recently been reported that in clinical isolates of P. aeruginosa, LasR is frequently mutated and nonfunctional, and RhlR independently acts to produce virulent factors that maintain toxicity. Thus, for effective treatment of chronic CF infections, RhlR antagonists is needed to prevent the LasR-independent Rhl system, but RhlR antagonists have rarely been reported. In this study, we found that curvularin, an aromatic compound with a cyclized alkyl side chain isolated from Phoma macrostoma, at a low micromolar concentration of 1–30 M potently and selectively inhibited pyocyanin and rhamnolipid production without affecting the cell viability of P. aeruginosa. Only high concentration (more over 100 M) curvularin negligibly inhibited biofilm formation and elastase production, suggesting that curvularin at low concentrations selectively inhibits RhlR. The QS antagonism by curvularin was investigated in experiments using QS competition and signaling molecules assays with QS gene expression analysis, and the results showed that, indeed, at low concentrations, curvularin selectively antagonized RhlR; in contrast, it negligibly antagonized LasR only when applied at a high concentration. The exclusive RhlR antagonizing activity of curvularin at low concentrations was confirmed using QS mutants; specifically, curvularin at low concentrations inhibited pyocyanin and rhamnolipid production by selectively antagonizing N-butanoyl homoserine lactone (BHL)-activated RhlR. Moreover, by targeting RhlR, curvularin reduced the in vivo virulence of wild-type P. aeruginosa as well as lasR mutants in Caenorhabditis elegans. Overall, low-concentration curvularin is an RhlR-exclusive antagonist in P. aeruginosa, and to the best of our knowledge, this is the first report describing an RhlR antagonist from natural resources. Hence, curvularin has great potential for the development of chronic P. aeruginosa infection therapeutics and for the study of RhlR function in the complex QS system.